A comparison of individual and combined l-phenylalanine ammonia lyase and cationic peroxidase transgenes for engineering resistance in tobacco to necrotrophic pathogens - Heather M. Way; Robert G. Birch; John M. Manners (Plant Biotechnology Reports, 2011)

Greater seed production in elevated CO 2 is not accompanied by reduced seed quality in Pinus taeda L. - DANIELLE A. WAY; SHANNON L. LADEAU; HEATHER R. MCCARTHY; JAMES S. CLARK; RAM OREN; ADRIEN C. FINZI; ROBERT B. JACKSON (Global Change Biology, 2010)
For herbaceous species, elevated CO 2 often increases seed production but usually leads to decreased seed quality. However, the effects of increased atmospheric CO 2 on tree fecundity remain uncertain, despite the importance of reproduction to the composition of future forests. We determined how seed quantity and quality differed for pine trees grown for 12 years in ambient and elevated (ambient+200 μL L −1 ) CO 2 , at the Duke Forest free‐air CO 2 enrichment (FACE) site. We also compared annual reproductive effort with yearly measurements of aboveground net primary productivity (ANPP), precipitation (P), potential evapotranspiration (PET) and water availability [precipitation minus potential evapotranspiration (P−PET)] to investigate factors that may drive interannual variation in seed production. The number of mature, viable seeds doubled per unit basal area in high‐CO 2 plots from 1997 to 2008 ( P 2 effect on mean seed mass, viability, or nutrient content. Interannual variation in seed production was positively related to ANPP, with a similar percentage of ANPP diverted to reproduction across years. Seed production was negatively related to PET ( P P P =0.88). This study adds to the few findings that, unlike herbaceous crops, woody plants may benefit from future atmospheric CO 2 by producing larger numbers of seeds without suffering degraded seed quality. Differential reproductive responses between functional groups and species could facilitate woody invasions or lead to changes in forest community composition as CO 2 rises.

Differential gene expression of wheat progeny with contrasting levels of transpiration efficiency - Gang-Ping Xue; C. Lynne McIntyre; Scott Chapman; Neil I. Bower; Heather Way; Antonio Reverter; Bryan Clarke; Ray Shorter (Plant Molecular Biology, 2006)